Anomalous longitudinal relaxation of nuclear spins in CaF2 - Kropf, Chahan; Fine, Boris V. (Fortschritte der Physik, 2017)
We consider the effect of non-secular resonances for interacting nuclear spins in solids which were predicted theoretically to exist in the presence of strong static and strong radio-frequency magnetic fields. These resonances imply corrections to the standard secular approximation for the nuclear spin-spin interaction in solids, which, in turn, should lead to an anomalous longitudinal relaxation in nuclear magnetic resonance experiments. In this article, we investigate the feasibility of the experimental observation of this anomalous longitudinal relaxation in calcium fluoride (CaF2) and conclude that such an observation is realistic.